2015
DOI: 10.1371/journal.pone.0123345
|View full text |Cite
|
Sign up to set email alerts
|

Participation Dynamics in Population-Based Longitudinal HIV Surveillance in Rural South Africa

Abstract: Population-based HIV surveillance is crucial to inform understanding of the HIV pandemic and evaluate HIV interventions, but little is known about longitudinal participation patterns in such settings. We investigated the dynamics of longitudinal participation patterns in a high HIV prevalence surveillance setting in rural South Africa between 2003 and 2012, taking into account demographic dynamics. At any given survey round, 22,708 to 30,495 persons were eligible. Although the yearly participation rates were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 43 publications
(36 reference statements)
2
46
1
Order By: Relevance
“…Another limitation is that some people eligible for HIV testing in the surveillance cannot be contacted in a specific year or refuse to test for HIV. However, over 5 years, more than 80% of eligible individuals tested for HIV at least once in the study population, 34 ensuring that, during the observation period, most people with HIV were included in our sample. We would expect that people who do not test for HIV have even lower rates of linkage to care and other cascade progressions than those in our study, suggesting that our conclusions are likely to be conservative.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that some people eligible for HIV testing in the surveillance cannot be contacted in a specific year or refuse to test for HIV. However, over 5 years, more than 80% of eligible individuals tested for HIV at least once in the study population, 34 ensuring that, during the observation period, most people with HIV were included in our sample. We would expect that people who do not test for HIV have even lower rates of linkage to care and other cascade progressions than those in our study, suggesting that our conclusions are likely to be conservative.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only 26–46% of the eligible South African participants contacted provided a blood sample for HIV testing, which may have affected estimates of the associations between ART coverage and incidence. 19 The Mombasa female sex workers study in Kenya reported that each 10% increase in ART coverage among all HIV-infected persons in the region was associated with a 23% reduction of HIV acquisition risk in female sex workers , but such regional coverage may not accurately reflect exposure among the male partners of the sex workers. 20 Neither the South African nor the Mombasa study assessed the associations of MMC coverage with HIV incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Africa Centre, virtually all eligible households were contacted and agreed to participate in the HIV surveillance. Moreover, almost all eligible residents were successfully contacted to request their participation in testing (e.g., 94.3% in 2009 [5]). Therefore, practically all missing data at the Africa Centre arise through individuals directly refusing to test.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, only 5.7% of eligible respondents could not be contacted [5]. The high contact rate is likely a result of the HIV survey operations, which include household revisits at later dates, after working hours, and on weekends.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation